Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India - Sruoga, Virginijus; Rocienė, Agnė (Zootaxa, 2018)
Three new species of Elachistidae: Elachistinae from northern India are described: Elachista arcuata sp. nov., Urodeta jurateae sp. nov., and U. pectena sp. nov. The new species are diagnosed and illustrated with photographs of the adults and genitalia.